The Effect of the Scientific Inquiry Learning Model on the Topic of the Respiratory System on the Critical Thinking Skills of Grade XI Senior High School Students - Hujaibah, Poojaa; Annas, Nirwana; Jayanti, Ummi Nur Afinni Dwi (Universitas Lampung, 2023)
This study aims to determine the effect of the application of the Scientific Inquiry learning model on students' critical thinking skills on the subject matter of the respiration system in XI grade. This research methodology uses quantitative methods with the type of quasi experiment. The study population amounted to 150 students from XI grade Senior High School 1 Sei Suka. The sample of this study consisted of 2 classes determined by cluster random sampling technique, namely X grade as an experimental class using the Scientific Inquiry learning model and X grade as a control class using conventional learning. The instruments used in this study are critical thinking ability test instruments totaling 11 essay test questions that have been validated by one validator and have been tested for item validity. The results showed that the average critical thinking skills of students in the experimental class taught using the Scientific Inquiry learning model were in the high category and the average critical thinking skills of students in the control class taught using the conventional learning model were in the low category, this is based on the average postest value of the experimental class which is 77.3443 and the control class which is 37.4957. The results of hypothesis testing using Independent Sample t-test statistics show that there is an effect of the Scientific Inquiry learning model on students' critical thinking skills on the material of the respiration system in XI grade.Keywords: critical thinking skills of students, scientific inquiry learning model, conventional learning